Menjaga Kearifan Lokal Dalam Era Globalisasi - Linda Ramisah; Nadila Ramadana; Luthfi Aulia; Eka Darliana; Anisa Noverita (Prodi Pendidikan IPS STKIP AL MAKSUM, 2026)
Local wisdom serves as the primary foundation of national identity, currently facing significant challenges amidst the rapid flow of globalization. This research aims to examine the importance of preserving local traditional values as a survival strategy in an increasingly anonymous and uniform modern era. Employing a qualitative approach with a literature study method, data were gathered from various scientific literatures, books, and relevant documents, which were then analyzed descriptively. The results indicate that local wisdom functions as a moral